Gmina jako płatnik podatku od towarów i usług - Pyrz, Michał (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
In the light of existing rules local government units can perform tasks by, among others, offices, budgetary units and local government budgetary establishment. These units, however, have a different legal status so their status at the level of law, including tax law, is varied. In this article, the author discusses the issues of subjectivity municipal local government units and public finance sector units through which the local government carries out tasks in the value added tax. The importance of the problem of interpretation of the provisions of the Act is best evidenced by the number of cases that deal with this issue. This is indicated by the fact that this issue was the subject of consideration of the Supreme Administrative Court
Keywords: podatek od towarów i usług; gmina; jednostka samorządu terytorialnego; jednostka budżetowa; zakład budżetowy; finanse publiczne